Plasma-assisted molecular beam epitaxy of GaN nanowires on epitaxial single-layer graphene - Fernandez-Garrido, Sergio; Ramsteiner, Manfred; Galves, Lauren A.; Sinito, Chiara; Corfdir, Pierre; Schiaber, Ziani de Souza [UNESP]; Lopes, Joao Marcelo J.; Geelhaar, Lutz; Brandt, Oliver; Chyi, J. I.; Fujioka, H.; Morkoc, H. (Spie-int Soc Optical Engineering, 2018)
We investigate the formation of GaN nanowires in plasma-assisted molecular beam epitaxy on epitaxial graphene prepared on SiC(0001) using the surface graphitization method in an inductively heated furnace. The pristine graphene layer structure is characterized by the presence of atomically flat terraces and steps which are covered by single-layer and bi-layer graphene, respectively. The formation of GaN is investigated under N-rich growth conditions for substrate temperatures between 725 and 800 degrees C. Regardless of the substrate temperature, graphene is found to degrade during GaN growth due to its exposure to the N plasma. The morphology of the samples varies significantly between the regions originally covered with single-layer and bi-layer graphene. Specifically, on the terraces GaN grows as a Ga-polar layer, while along the step edges it forms meandering rows of N-polar nanowires. The formation of N-polar GaN nanowires on the cation-polar SiC substrate is explained in terms of a C-induced polarity inversion. Due to the superior thermal stability of N-polar material, it is possible to exclusively form nanowires along the step edges when using elevated substrate temperatures. Therefore, the investigated graphene layer structure enables the self-assembled formation of well-separated rows of GaN nanowires.
Keywords: group-III nitrides; III-V semiconductors; nanowire; polarity junction; polarity inversion; polarity-induced selective area epitaxy